The incumbency disadvantage in South Korean National Assembly elections: Evidence from a regression discontinuity approach. (April 2017) - Roh, Jungho
Abstract: In marked contrast to the findings from advanced democracies that incumbent office holders enjoy electoral advantages, this study finds that a substantial incumbency disadvantage exists in South Korean National Assembly (KNA) elections. I employ a quasi-experimental regression discontinuity design to distinguish the true effects of incumbency from the selection effects associated with candidate qualities, such as charisma and ability levels. My results show that serving a term in office reduces the probability of winning by around 20–30 percentage points and reduces the vote share by about 3–7 percentage points. Possible reasons for the incumbency disadvantage are briefly discussed, with an emphasis on the particularly high level of public discontent with governing elites in the KNA due to what voters perceive to be their widespread corruption.